Parallel Picture-Naming Tests: Development and Psychometric Properties for Farsi-Speaking Adults. Issue 2 (4th March 2017) - Tahanzadeh, Behnoosh; Soleymani, Zahra; Jalaie, Shohre
ABSTRACT: The present study describes the development and validation of two parallel picture-naming tests (PPNTs) as neuropsychological tools for evaluating word retrieval disorders in Farsi-speaking adults with and without aphasia. The development phase used the distributions of psycholinguistic variables (word frequency or age of acquisition) to select test items. Each parallel test consists of 109 line-drawings assigned to concrete nouns that were arranged in order of increasing difficulty. Assessment of content validity indicated that all items were quite or highly relevant and clear. The psychometric features were tested on 30 normal adults and 10 matched individuals with aphasia. The results showed appropriate criterion validity. Parallel tests allowed discrimination by subjects with and without naming difficulties. The tests were internally consistent. Each test form showed reasonable test-retest reliability. The correlation between the scores from both test forms indicated good parallel reliability. The cut-off point at which the tests reached the highest level of sensitivity and specificity was observed to be 86 correct responses. The percentage of correct responses for each item correlated strongly with frequency, age of acquisition, and name agreement. The overall findings support the validity and reliability of the PPNTs and suggest that these tests are appropriate for use in research and for clinical purposes.